The Impact of Youtube's Beauty Vlogger on Consumer Buying Decision (The Case of University Students) - Putri, Safir Dzakiyyah Aziziyah (APPS Publications, 2022)
Advancement in technology has brought a lot of changes in many aspects of life. Currently, there are trends of YouTube’s Beauty Vlogger where they share videos on how to apply makeup or information on a beauty product through tutorials or by reviewing with clear presentations and attractive visuals as a way to influence women to be interested in using these beauty products. It cannot be denied that these trends have been supporting a lot of existing businesses. The purpose of this research is to analyze the influence of YouTube’s Beauty Vlogger with its three dimensions of Attractiveness, Trustworthiness, and Expertise towards consumer buying decision. The data collection technique uses random sampling which produces data from people who are beauty enthusiasts. There were 57 respondents for this research after the researcher distributed the questionnaires through several social media platforms. The researcher used SPSS as the data analysis technique. The result of this research shows that YouTube’s beauty vlogger significantly influenced the consumer buying decision. Although the relationships between the influencer’s attractiveness, trustworthiness, expertise, and consumer buying interest have been examined in past research, the specific relationships examined in this study have not yet been previously investigated using YouTube vloggers in Indonesia and a sample of the country’s young people.